High leverage practices for inclusive classrooms - McLeskey, James, 1949-; Maheady, Lawrence; Billingsley, Bonnie S.; Brownell, Mary T.; Lewis, Timothy J., 1960- (New York : Routledge, 2019)
High Leverage Practices for Inclusive Classrooms offers a set of practices that are integral to the support of student learning, and that can be systematically taught, learned, and implemented by those entering the teaching profession. The book focuses primarily on Tiers 1 and 2, or work that mostly occurs with students with mild disabilities in general education classrooms; and provides rich, practical information highly suitable for teachers, but that can also be useful for teacher educators and teacher preparation programs. This powerful, research-based resource offers twenty-two brief, focused chapters that will be fundamental to effective teaching in inclusive classrooms.
Collaborating with colleagues to increase student success / Marilyn Friend & Tammy Barron -- Leading effective meetings with professionals and families / Jocelyn Washburn & Bonnie Billingsley -- Collaborate with families to support students learning and secure needed services / Mayumi Hagiwara & Karrie A. Shogren -- Using multiple sources of information to develop a comprehensive understanding of a student's strengths and needs / Amber Benedict, Kyena Cornelius, & Kelly Acosta -- Interpreting and communicating assessment information with stakeholders to collaboratively design and implement educational programs / Margaret Kamman & Erica D. McCray -- Using student assessment data, analyzing instructional practices, and making necessary adjustments that improve student outcomes / Erica S. Lembke, R. Alex Smith, Cathy Newman Thomas, Kristen L. McMaster, and Erica N. Mason -- Consistent, organized, respectful learning environment / Talida State, Barbara S. Mitchell, and Joseph Wehby -- High leverage practice : using geedback to improve dtudent outcomes / Allison Bruhn, Jennifer Freeman, Regina Hirn, Lee Kern -- Teaching social skills / Sara McDaniel, Imad Zaheer, and Terrance M. Scott -- Conducting functional behavior assessments to develop individualized behavior support plans / Blair Lloyd, Howard Wills, and Timothy J. Lewis -- Identify and prioritize long- and short-term learning goals / Sheila R. Alber-Morgan, Moira Konrad, Terri Hessler, Maria R. Helton, and Alana Oif Telesman -- Systematically design instruction toward a specific learning goal / Moira Konrad, Terri Hessler, Sheila R. Alber-Morgan, Carrie A. Davenport, and Maria R. Helton -- Adapt curriculum tasks and materials for specific learning goals / Sheila R. Alber-Morgan, Maria R. Helton, Alana Oif Telesman, and Moira Konrad -- Teaching cognitive and metacognitive strategies to support learning and independence / Shannon Budin, Angela L. Patti, & Lisa A. Rafferty -- Provide scaffolded supports / Troy Mariage, Judith Winn, and Arfang Dabo -- Use explicit instruction / Charles A. Hughes, Paul J. Riccomini, Jared R. Morris -- Using flexible grouping / Larry Maheady, Tim Zgliczynski, & Gliset Colón -- Use strategies to promote active student engagement / William L. Heward -- Use assistive and instructional technologies / Maya Israel -- Provide intensive instruction / Devin Kearns, Marney S. Pollack, and Victoria M. Whaley -- Teach students to maintain and generalize new learning across time and settings / Mary Catherine Scheeler, David L. Lee, and Andrew M. Markelz -- Providing positive and corrective feedback / Kristen Merrill O'Brien, Michelle M. Cumming, and Elizabeth Bettini -- Some final thoughts regarding high leverage practices.
Keywords: Inclusive education; Classroom management; Children with disabilities -- Education; EDUCATION / Administration / General; EDUCATION / Organizations & Institutions